1995
DOI: 10.1136/bmj.310.6979.569
|View full text |Cite
|
Sign up to set email alerts
|

Randomised trial of lipid lowering dietary advice in general practice: the effects on serum lipids, lipoproteins, and antioxidants

Abstract: Objective-To determine the relative efficacy in general practice of dietary advice given by a dietitian, a practice nurse, or a diet leaflet alone in reducing total and low density lipoprotein cholesterol concentration.Design-Randomised six month parallel trial. Setting-A general practice in Oxfordshire. Subjects-2004 subjects aged 35-64 years were screened for hypercholesterolaemia; 163 men and 146 women with a repeat total cholesterol concentration of6*0-8-5 mmol/l entered the trial.Interventions-Individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 22 publications
1
67
0
2
Order By: Relevance
“…Unfortunately, there is probably only one study that determined the relative efficacy of different strategies of giving dietary advice in general practice. Neil et al (33) reported that lipid-lowering dietary advice given by a dietitian or a practice nurse or a diet leaflet alone resulted in equally small effects on lipid concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there is probably only one study that determined the relative efficacy of different strategies of giving dietary advice in general practice. Neil et al (33) reported that lipid-lowering dietary advice given by a dietitian or a practice nurse or a diet leaflet alone resulted in equally small effects on lipid concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…While demonstrating that improvements in diet can be achieved, the deterioration in dietary habits between 12 weeks and 1 y observed in the intervention group suggests the need for a more sustained programme to maintain improvements. Available evidence suggests that delivery of advice must be carefully focused to produce behavioural change (Neil et al, 1995). The present study did not ration advice to individuals assessed as 'ready to change'.…”
Section: Overall Conclusionmentioning
confidence: 86%
“…The trials lasted from 3 months (short duration) to over 5 years (long duration). Most of the trials measured changes in total cholesterol and other risk factorsÐ blood pressure, smoking, weight, and dietary habits (Jones, Davies, Dove et al 1988, Bennet, Blackall, Clapham et al 1989, Robertson, Phillips, Mant et al 1992, Gibbins, Riley and Brimble 1993, Oxcheck study 1995, Roderick, Ruddock, Hunt et al 1997, Yasmin, Mascie-Taylor, Brown et al 1998, and two trials also measured lipid pro® les including HDL, LDL and triglycerides (Baron, Gleason, Crowe et al 1990, Neil, Roe, Godlee et al 1995.…”
Section: Trials At General Practicesmentioning
confidence: 96%
“…An Oxfordshire trial (Neil et al 1995) involving 163 men and 146 women aged between 35± 64 years examined the extent of reduction in total cholesterol and LDL cholesterol concentrations after dietary advice was given in one of three ways; by a dietician, or a practice nurse, or through a diet lea¯et alone. The adults were randomly assigned to one of the three groups.…”
Section: Trials On Normal Healthy Individualsmentioning
confidence: 99%